Cl*-CONNECTEDNESS AND Cl − Cl*-CONNECTEDNESS IN IDEAL TOPOLOGICAL SPACES - Tyagi, Brij Kishore; Bhardwaj, Manoj; Singh, Sumit (Matematichki Bilten, 2018)
In this paper, new types of connectedness of ideal topological space \(X\) and their relationships with other existing connectednesses are discussed.